Mathematics Communication Ability in Mathematics Learning in Pandemic Times - Indra Martha Rusmana; Kartono Kartono; Zainuri Zainuri; Masrukan Masrukan (International Conference on Science, Education, and Technology, 2021)
The pandemic period that has lasted for one year has made the face of education in this country experience significant changes, one of which is the learning process carried out by distance learning through an online system by utilizing various available platforms. This makes changes in various cognitive abilities of students, including students' mathematical communication skills. Mathematical communication skills in learning mathematics are very necessary. This is because mathematical communication can explain and organize the thinking skills possessed by students, both orally and in writing. A student who has good communication skills can provide the right response between students and other students through the media used in learning. The purpose of this paper is to present the understanding of mathematical communication skills with the scope of two things, namely the ability of students to use mathematics as a communication tool (mathematical language), and the ability of students to communicate the mathematics learned as the content of the message that must be conveyed. How and why communication is important to build a mathematical community through open communication channels in the classroom, especially during a pandemic.